The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1542/peds.2006-3160
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Computerized Prescriber Order Entry on the Incidence of Adverse Drug Events in Pediatric Inpatients

Abstract: This study demonstrated that a computerized physician order entry system with substantive decision support was associated with a reduction in both adverse drug events and potential adverse drug events in the inpatient pediatric population. Additional system refinements will be necessary to affect remaining adverse drug events. Preventable events did not predict excess length of stay and instead may represent a sign, rather than a cause, of more complicated illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 31 publications
1
106
2
1
Order By: Relevance
“…Of the studies reporting preventable ADEs, 1,40,45,62,66,73 2 studies 1,45 reported statistically significant decreases in ADEs after an intervention: a 77% reduction in preventable ADE prescribing errors using multiple error reduction strategies (n = 16 of 12 026 pre versus 3 of 9187 post) and a 43% reduction in all types of preventable ADE errors using CPOE with CDS (n = 46 of 1197 pre versus 26 of 1210 post), respectively. Two of the other studies 40,66 reported only 1 preventable ADE during their respective pre-and postintervention periods, and a third study 62 reported 2 preventable ADEs, 1 during the pre-and 1 during the postintervention periods.…”
Section: Aggregate Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Of the studies reporting preventable ADEs, 1,40,45,62,66,73 2 studies 1,45 reported statistically significant decreases in ADEs after an intervention: a 77% reduction in preventable ADE prescribing errors using multiple error reduction strategies (n = 16 of 12 026 pre versus 3 of 9187 post) and a 43% reduction in all types of preventable ADE errors using CPOE with CDS (n = 46 of 1197 pre versus 26 of 1210 post), respectively. Two of the other studies 40,66 reported only 1 preventable ADE during their respective pre-and postintervention periods, and a third study 62 reported 2 preventable ADEs, 1 during the pre-and 1 during the postintervention periods.…”
Section: Aggregate Data Synthesismentioning
confidence: 99%
“…Five studies examined the effect of CPOE with CDS for multiple medications on inpatients 45,46,51,73,88 and found a 14% increase in errors to a 99% decrease in all types of errors. The study reporting a 14% increase in all types medication errors 73 noted that this change was non-statistically significant (P .…”
Section: Data Synthesis For Specific Interventionsmentioning
confidence: 99%
“…Electronic medication prescribing and atuomated dose checking [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Computerized physician order entry (n = 5)…”
Section: Intervention Type Example Of Intervention Referencesmentioning
confidence: 99%
“…While this information suggests that national organizations encourage CPOE adoption and use of CPOE in children's hospitals is not entirely uncommon, higher levels of use among hospitals that care for children will likely be needed to achieve the IOM goals of redesigning our healthcare system. Current research focused on CPOE use in hospitals that care for children has demonstrated improvements in safety of care with an overall reduction in medication errors [7][8][9][10]. While improvements in medical errors are almost uniformly found with the use of CPOE, the improvement in costly adverse drug events was only found in one of the studies.…”
Section: Introductionmentioning
confidence: 99%
“…While improvements in medical errors are almost uniformly found with the use of CPOE, the improvement in costly adverse drug events was only found in one of the studies. [8] Nonetheless, improvements in medication administration represent a very important opportunity in pediatrics because children are at high risk of medication errors because medications are often delivered with weightbased prescribing and frequently used off-label, resulting in a greater potential for error [11]. Despite this opportunity for medical safety, Han et al published a study in 2005 that demonstrated an association between CPOE use in a Pediatric Intensive Care Unit with an increase in patient mortality [12].…”
Section: Introductionmentioning
confidence: 99%